Planning and design for low carbon development in a sensitive landscape: a Douro Valley setting for the YPP workshop - Lourenço, Júlia M. (2009)
Selecting the Douro Valley as the location of the Young Planning Professionals (YPP) workshop posed a challenge. Given the remoteness of this area, its low population densities and its corresponding low carbon emissions, and also its outstanding landscape, this was perhaps not the most obvious place as the location for a discussion about low carbon cities. But in other respects, this is a good location for such a brainstorm. The potential advantage is the innovative planning approach provided by the YPP Workshop, with its randing potential for the region. For ISOCARP the exercise provides an input to the Society’s growing knowledge about energy resources issues and sustainable spatial planning.